The Needs for Developing High-Efficiency Learning Management in the Digital Era - Pimjai, Kanchit; Traiwichitkhun, Duangkamol (Journal of Education Studies, Chulalongkorn University, 2024)
This research aims to 1) study the conceptual framework for high-efficiency learning management in the digital era, and 2) investigate the needs for developing high-efficiency learning management in the digital era. The study employs a mixed-methods research design divided into two phases. Phase 1 involves qualitative research to address the conceptual framework for high-efficiency learning management in the digital era, with data collected from four selected experts using purposive sampling. The research tool was an interview guide, and the qualitative data was analyzed through content analysis, categorization, and summarization of findings. Phase 2 involves quantitative research to address the needs for developing high-efficiency learning management in the digital era, with a sample group of 112 school administrators and teachers selected through simple random sampling. The research tool was a questionnaire, and quantitative data analysis was conducted using mean, standard deviation, and modified priority needs index. The findings demonstrate that: 1) The conceptual framework for high-efficiency learning management in the digital era include curriculum development, learning management, learning media and technology, and learning assessment. 2) The needs for developing high-efficiency learning management in the digital era is developing school curricula that respond to changes in the digital era.